Nuclear Material Performance 2016
DOI: 10.5772/62434
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten-Based Composites for Nuclear Fusion Applications

Abstract: This chapter provides a comprehensive knowledge about the potential role of tungstenbased composites in fusion reactors and the research work which has been done in this very important area of nuclear materials. The characteristics of tungsten, which make it the most potential candidate for plasma-facing applications, have been presented along with the shortcomings in pure tungsten. The research work that has been done so far in the field of tungsten-based composites to overcome the problems with pure tungsten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…In addition, the mechanical alloying method can also combine and mix materials that have a high melting point with a low melting point [16] [17]. Previous studies have reported by Owais A et al [18] that nuclear fusion devices such as WTaTiVCr at high temperatures and having a high melting point exhibit high mechanical properties. In addition, this type of HEA has recently been investigated such as TixWTaVCr [19],…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mechanical alloying method can also combine and mix materials that have a high melting point with a low melting point [16] [17]. Previous studies have reported by Owais A et al [18] that nuclear fusion devices such as WTaTiVCr at high temperatures and having a high melting point exhibit high mechanical properties. In addition, this type of HEA has recently been investigated such as TixWTaVCr [19],…”
Section: Introductionmentioning
confidence: 99%
“…first walls) of nuclear fusion reactors are made of W, in order to hold the strength at extremely high temperatures and shield energetic α-and γ-radiations [2]. However, high brittleness is a disadvantage of W. In the nuclear reactor's high temperature and high radiation environment, the surface of W can be eroded by high-energy rays quickly and generates dust, which affects the plasma parameters [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten-based composites are a significant in the field of nuclear materials. They can improve mechanical properties, oxidation resistances, irradiation resistance, strength and microstructural stability (Waseem and Ryu, 2016).…”
Section: Introductionmentioning
confidence: 99%